2019
DOI: 10.1038/s41467-019-11982-4
|View full text |Cite
|
Sign up to set email alerts
|

Neural JNK3 regulates blood flow recovery after hindlimb ischemia in mice via an Egr1/Creb1 axis

Abstract: Diseases related to impaired blood flow such as peripheral artery disease (PAD) impact nearly 10 million people in the United States alone, yet patients with clinical manifestations of PAD (e.g., claudication and limb ischemia) have limited treatment options. In ischemic tissues, stress kinases such as c-Jun N-terminal kinases (JNKs), are activated. Here, we show that inhibition of the JNK3 (Mapk10) in the neural compartment strikingly potentiates blood flow recovery from mouse hindlimb ischemia. JNK3 deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…The results showed that there is significant induction of p-Akt1 (S473), p-Akt-Pan (S472, S473, S474), p-CREB (S133), p-ERK1 (T202/Y204), p-ERK2 (T185/Y187), and p-GSK3α/β (S21/S9) expression in rA2 treated HBMEC ( Figure 3A ). CREB is the transcription factor that regulates vascular remodeling via mediating downstream growth factors, including VEGF ( Kant et al, 2019 ). To analyze whether rA2 treatment induces the protein levels of p-CREB, VEGF, and BDNF in HBMEC, western blotting analysis was used.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that there is significant induction of p-Akt1 (S473), p-Akt-Pan (S472, S473, S474), p-CREB (S133), p-ERK1 (T202/Y204), p-ERK2 (T185/Y187), and p-GSK3α/β (S21/S9) expression in rA2 treated HBMEC ( Figure 3A ). CREB is the transcription factor that regulates vascular remodeling via mediating downstream growth factors, including VEGF ( Kant et al, 2019 ). To analyze whether rA2 treatment induces the protein levels of p-CREB, VEGF, and BDNF in HBMEC, western blotting analysis was used.…”
Section: Resultsmentioning
confidence: 99%
“…Creb1 could bind to Egr1 promoters [ 27 ]. As a member of the bZIP superfamily, the cAMP response element-binding protein 1 (Creb1) was observed improving interaction with Erg1 after hypoxia [ 42 ]. Creb1 and Egr1 exhibited a synergistic role in governing MAO-B gene expression under basal and dopamine-induced conditions [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, JNK signaling pathway has been shown to play critical roles in regulating cell fate, being implicated in a multitude of diseases ranging from cancer to ischemic immunological/inflammatory conditions . JNKs cause changes to gene transcription, resulting in biological responses such as inflammation and/or apoptosis . Many effects of JNKs are mediated by transcription factors of the activator protein‐1 family, of which c‐Jun is the most commonly known.…”
Section: Discussionmentioning
confidence: 99%